The occurrence and prevalence of potentially zoonotic enteropathogens in - Kemper, Nicole; Aschfalk, Ansgar; Höller, Christiane (Rangifer, 2004)
The information about pathogens excreted by semi-domesticated reindeer (Rangifer tarandus tarandus) that might represent a health risk to humans and animals is insufficient. The objectives of this study are to find the occurrence and prevalence of important potentially enteropathogenic, zoonotic bacteria and parasites in reindeer. Faecal samples from clinically healthy, semi-domesticated reindeer (n=2243) from northern regions of Finland and Norway were examined for important potentially enteropathogenic bacteria (Campylobacter spp., Enterococcus spp., Escherichia coli, Salmonella spp. and Yersinia spp.) and parasites (Cryptosporidium spp.) following standard procedures. Escherichia coli were isolated in 2123 (94.7%), Enterococcus spp. in 2084 (92.9%), Yersinia spp. in 108 (4.8%) samples and Campylobacter sp., identified as C. hyointestinalis, in one sample only (0.04%). Neither Salmonella spp. nor Cryptosporidium-oocysts were detected. This study clearly shows that E. coli and Enterococcus spp. belong to the normal intestinal flora of healthy reindeer. However, only few of the isolated E. coli-strains possess genes encoding stx1 (0.14%), stx2 (0%), eae (0.52%) and hlyEHEC (0.99%), detected by PCR, that have the ability to cause health problems in humans and also animals. The isolated Yersinia spp. were further analysed for virulence factors, but examinations revealed no pathogenic strains. The public health risk due to excretion of important enteropathogenic microorganisms from reindeer has to be considered very low at present but a putative epidemiological threat to human health might arise when herding conditions are changed towards intensification and crowding. This study was performed as part of the EU-project RENMAN (www.urova.fi/home/renman/). Abstract in Norwegian / Sammendrag: Det er mangelfull kunnskap om hvorvidt det i reinmøkk kan finnes mikroorganismer som kan representere en helserisiko for dyr og mennesker. Hensikten med denne studien var å undersøke forekomsten av mulige sykdomsfremkallende mikroorganismer i reinmøkk. Prøver av reinmøkk ble samlet fra 2243 klinisk friske tamrein i nordre deler av Finland og Norge. Prøvene ble undersøkt for bakteriene Campylobacter spp., Enterococcus spp., Escherichia coli, Salmonella spp., Yersinia spp. og parasitten Cryptosporidium spp. ved bruk av standardiserte laboratoriemetoder. E. coli ble funnet i 2123 prøver (94,7%), Enterococcus spp. i 2084 prøver (92,9%) og Yersinia spp. i 108 prøver (4,8%). Campylobacter spp., identifisert som Campylobacter hyointestinalis, ble bare funnet i én prøve (0,04%). Salmonella spp. og Cryptosporidium spp. ble ikke påvist. Videre undersøkelser av E. coli viste at bare svært få (<1%) av isolatene hadde gener som kodet for mulige sykdomsfremkallende toksiner. Videre undersøkelser av Yersinia spp. viste at ingen av disse isolatene var sykdomsfremkallende. Studien viser at helserisikoen knyttet til de undersøkte mikroorganismene i reinmøkk må betraktes som svært liten.